Modeling the Relationship Between Employee Conflict, Work Stress, and Turnover Intention in the Food-Service Industry - Josephine Diana S. Campos; Jofrey Ramos Campos (People and Behavior Analysis, 2024)
The fast-paced and demanding food service industry faces challenges like employee conflict, workplace stress, and high turnover intentions, which impact both employee well-being and business performance. This study examines the causal relationships among employee conflict, work stress, and turnover intention using Partial Least Squares Structural Equation Modeling (PLS-SEM). A sample of 237 food service restaurant workers from Pampanga, Philippines, was selected via purposive sampling. Data were collected using a survey instrument with rating scales. The study evaluated the model’s fit, internal reliability, and construct validity using confirmatory factor analysis. Path analysis revealed a moderate fit of the model to the data, indicating acceptable reliability and validity. Findings showed a direct positive effect of employee conflict on turnover intention, with work stress having an indirect influence. Recommendations include the following:  implementing conflict resolution and stress management programs, improving communication, offering flexible work hours, task management, employee assistance programs, rewards, and career advancement opportunities. Due to geographical limitations, future studies should also employ qualitative or mixed methods and longitudinal designs to examine these effects over time.